Combined effects of piston bowl geometry and spray pattern on mixing, combustion and emissions of a diesel engine: A numerical approach. (1st August 2018) - Khan, Shahanwaz; Panua, Rajsekhar; Bose, Probir Kumar
Highlights: Effects of spray angle and chamber geometry analyzed numerically. The piston bowl geometry could generate strong squish influencing air-fuel mixing. The fuel spray pattern across the combustion chamber influences combustion. The improved air-fuel mixing reduces the brake specific fuel consumption. Abstract: In the present work the combine effects of spray angle and the piston bowl geometry on mixing, combustion and emission characteristics of a direct injection diesel engine have been analyzed numerically. The piston bowl geometry is one of the most important factor that affect the air fuel mixing and combustion and emissions in a direct injection diesel engine. Four spray angles 150°, 155°, 160° and 165° and three different piston bowl geometries namely Toroidal Re-entrant Combustion Chamber (TRCC), Toroidal Combustion Chamber (TCC) and the baseline Hemispherical Combustion Chamber (HCC) have been considered for the same compression ratio of 17.5 and with same chamber volume for all three cases. To simulate the in-cylinder flow and combustion computational fluid dynamics (CFD) modeling based AVL FIRE code was performed and experimental results of the baseline hemispherical bowl were used to validate the numerical model. Simulation results show that spray angle significantly affects the mixing and combustion process for all three bowl geometries and the engine having TRCC type of combustion chamber gives better performance.